PENGARUH MARKETING EMPLOYEE TERHADAP VOLUME PENJUALAN SEPEDA MOTOR (Studi Pada PT. Krida Dinamik Autonusa Sumbawa Besar) - Ika Fitriyani; Lola Ayuni Purnanda; Setio Hadi (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of employee marketing on sales volume of Honda motorcycles at PT. Autonusa Krida Dynamics, Sumbawa Besar Branch. The type of research used is associative research. The type of data used is quantitative data in the form of marketing employees and sales volume of Honda motorcycles obtained from documents and archives of the annual report of PT. Autonusa Krida Dynamics, Sumbawa Besar Branch for the 2017-2021 period. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t-test), and determination coefficient test (R2). The results of this study indicate that employee marketing has a positive and significant effect on motorcycle sales volume at PT. Autonusa Krida Dynamics, Sumbawa Besar Branch. The degree of influence of employee marketing on motorcycle sales volume at PT. The Autonusa Krida Dynamics of the Sumbawa Besar Branch is 22.4%, while the remaining 77.6% is influenced by other variables beyond the reach of this study. Sales volume of a company is closely related to the quality of marketing employees. One form of approach in an effort to increase the company's sales volume and the quality of human resources in the field of marketing is through education and providing motivation. Therefore, efforts are made for the company to always provide education, training and motivate employees so that the company's sales results can increase.